OPTIMAL DESIGN OF GEOTECHNICAL STRUCTURES FOR LOWLAND AREAS - S. Valliappan; A. Hakam; V. Tandjiria (Lowland Technology International, 1999)
The applications of optimization technique for raft foundations built on soft soils and retaining walls are presented in this paper. The objective function of the optimization problem is the cost of the structures (which is a function of thickness, dimensions and material of stabilized soil). The constraints are the displacement, differential displacement and stabilities. The finite difference sensitivity analysis and the combination of extended bi-point constraint and Lagrangian constraint approximation are carried out during the structural optimization process. The finite element method has been used to analyse the response of the structures. The results of the numerical examples show that the structures can be designed both economically and effectively using the proposed method.